Measurement of Muon Neutrino Quasielastic Scattering on a Hydrocarbon Target at E-v similar to 3.5 GeV - Fiorentini, GA (2013)
This work was supported by the Fermi National Accelerator Laboratory under United States Department of Energy (DOE) Office of High Energy Physics Contract No. DE-AC02-07CH11359 which included the MINERvA construction project. Construction support also was granted by the United States National Science Foundation (NSF) under Grant No. PHY-0619727 and by the University of Rochester. Support for participating scientists was provided by NSF and DOE (USA) by CAPES and CNPq (Brazil), by CoNaCyT (Mexico), by CONICYT (Chile), by CONCYTEC, DGI-PUCP, and IDI/IGI-UNI (Peru), by Latin American Center for Physics (CLAF) and by RAS and the Russian Ministry of Education and Science (Russia). We thank the MINOS Collaboration for use of its near detector data. Finally, we thank the staff of Fermilab for support of the beam line and detector.